Typii Petropolitanum brasiliensium : a catalog of Brazilian types of bryophyta deposited at Komarov Botanical Institute (Le) in St. Petersburg, Russia - Câmara, Paulo Eduardo Aguiar Saraiva (2017)
The herbarium LE of the Komarov Botanical Institute in Saint Petersburg (former Leningrad), Russia holds one of the least known Brazilian moss collections in the world. In this paper we provide a list the Brazilian types of mosses deposited in the type collection of LE. Totaling types for 41 species names from Brazil are listed.